Youth Decision Making in Selecting Entrepreneurship as A Career - Sarah, Mia; Akbari, Taufan Teguh (Journal of Communication and Public Relations, 2022)
This research was conducted to determine Decision Making in Choosing Entrepreneurship as a Career Field. The theory used is Ginzberg's career development theory. This theory was chosen because it relates to a person's decision making process in choosing a career, there are two groups of young people in this study, namely the first group informants who have just finished their education directly become entrepreneurs and the second group informants work first in a new company to become entrepreneurs. This study examines the reasons for the decision making of young people who are confident of becoming entrepreneurs at a young age. The results obtained from this study were that the informants had aspired and wanted to become entrepreneurs since they were little, then encouragement from family and friends that made them confident of being an entrepreneur, and making their past job as valuable experiences and lesson that can be applied in the business of the informant themselves, even though many challenges were faced, they all became valuable lessons for young generation and make it experience.